Q-HCC - Quality-assured data set for hepatocellular carcinoma [data] - Sirazitdinov, Andrei (Universität, 2025)
Open multimodal dataset of hepatocellular carcinoma (HCC), which includes both image data (contrast-enhanced CT and MRI images) and tabular data (will be uploaded later).
Gesehen am 05.02.2025
Keywords: Forschungsdaten; Datenbank